CCNP wireless (642-737 IAUWS) quick reference - Henry, Jerome (Cisco Press, 2012)
As a final exam preparation tool, the CCNP Wireless (642-737 IAUWS) Quick Reference provides a concise review of all objectives on the new exams. The short eBook provides readers with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on concepts and commands that apply to this exam. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you focus your study on areas of weakness and enhancing your memory retention of essential exam concepts. The Implementing Advanced Cisco Unified Wireless Security exam is the exam associated with the CCNP Wireless certification. This exam assesses a candidate's capability to secure the wireless network from security threats via appropriate security policies and best practices, to properly implement security standards, and to properly configure wireless security components.
Online resource; title from PDF title page (Safari, viewed Sept. 26, 2012)
Keywords: Telecommunications engineers -- Certification; Electronic data processing personnel -- Certification; Wireless LANs -- Study guides -- Examinations; Computer networks -- Study guides -- Examinations; Réseaux locaux sans fil; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Computer networks; Examinations; Electronic data processing personnel; Certification; Telecommunications engineers; Certification; Study guides